2018
DOI: 10.17221/40/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colostrum composition on passive calf immunity in primiparous and multiparous dairy cows

Abstract: ABSTRACT:The aim of this study was to determine the effect of colostrum quality and composition on passive calf immunity in primiparous and multiparous dairy cows. Twenty-four primiparous and 24 multiparous dairy cows were used in this study. Calves born from primiparous dairy cows comprised the first group and calves born from multiparous dairy cows constituted the second group. After birth, colostrum samples were immediately taken from dairy cows. Venous blood samples were collected from the calves before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
19
2
Order By: Relevance
“…Also, the obtained results are higher than that found by Abd El -Fattah et al (2012) who found that bovine colostrum contained 1.196 mg/ml lactoferrin and 32.33 mg/ml IgG. Aydogdu and Guzelbektes (2018) found that the protein, fat and IgG levels in bovine colostrum were 16.51-18.12%, 5.44 -7.46% and 73.81 -117.45 g/l, respectively. There was a positive correlation among colostrum IgG and total protein.…”
Section: Chemical Composition Of Raw Materialscontrasting
confidence: 70%
“…Also, the obtained results are higher than that found by Abd El -Fattah et al (2012) who found that bovine colostrum contained 1.196 mg/ml lactoferrin and 32.33 mg/ml IgG. Aydogdu and Guzelbektes (2018) found that the protein, fat and IgG levels in bovine colostrum were 16.51-18.12%, 5.44 -7.46% and 73.81 -117.45 g/l, respectively. There was a positive correlation among colostrum IgG and total protein.…”
Section: Chemical Composition Of Raw Materialscontrasting
confidence: 70%
“…GGT is found in very low concentrations in the blood of newborn calves but is rapidly absorbed from the colostrum before the gut closes, and hence, is a good indicator of colostrum ingestion (Braun et al ., 1982; Weaver et al ., 2000). The level of GGT has been also proposed as an indicator of passive immunity transfer (Parish et al ., 1997; Wilson et al ., 1999; Aydogdu and Guzelbektes, 2018). Different GGT thresholds for FPIT have been suggested (Perino et al ., 1993; Parish et al ., 1997; Hogan et al ., 2015; Cuttance et al ., 2017 a ), but the threshold is yet to be firmly established (Cuttance et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The mean birth weight of calves from control group was 38 kg and calves from experimental group -36 kg. Therefore, at every feeding colostrum were given in amount of 2 liters that made up 5 % of body weight (Aydogdu et al, 2018).…”
Section: Animals Housing and Managementmentioning
confidence: 99%